Dynamic Model of Risk Management of Electronic Waste in DKI Jakarta – Indonesia - et al., Dino Rimantho (International Journal of Advanced Science and Technology, 2020)
E-waste sustainable management is one of the biggest challenges in the 21st century. E-waste management is a complex and dynamic system. Therefore, the computer dynamics system model used in this study to predict the potential failure risk of e-waste management. The risk on each factor and sub-factor was assessed by applying the Failure Mode Effect Analysis method and the intervention weight was obtained from the Analytical Hierarchy Process method. The results showed an increase in risk in each factor from 2019 to 2028. The results of model validation also showed that all the models in each factor have met the validity criteria because their values range from 0.054 to 0.062. The pessimistic scenario did not show a difference in risk, but the moderate scenario displayed that the change in risk value in 2028 was around 1.333 points after the intervention. The optimistic scenario also showed a significant change in the value of risk in 2028, i.e. around 1556.5 points. The research still needs to be done to achieve more detailed and comprehensive results, especially the ones dealing with a number of quantitative data in order to obtain a more sustainable model of e-waste management.